The Spirit Of Seeking Knowledge In The Poem "Safir Tājid 'Iwaḍon 'Amman Tufāriquhu": A Rhetorical Analysis And Hermeneutic Of Imam Syafi'i’s Work: Rūḥ al-Baḥth 'An al-‘Ilm Fī al-Shi‘r "Safīr Tājid 'Iwāḍon 'Amman Tufāriquhu": Anālīsīs Rīṭōrīkiyya wa Hermīnūṭīkā Li-A‘māl Imām Syāfi'ī - Anestia, Yola; Wahyudi, Jarot (An-Nahdah Al-'Arabiyah, 2025)
This study examines the rhetorical aspects of the poem "Safir Tājid 'Iwaḍon 'Amman Tufāriquhu" by Imam Syafi'i to understand the spirit of seeking knowledge in Islamic tradition. Employing rhetorical and hermeneutic analysis, the methodology used is qualitative-descriptive with content analysis techniques  . The findings reveal three main points: (1) the use of beautiful, layered language and various rhetorical techniques such as metaphor and personification to emphasize the importance of knowledge; (2) profound philosophical meanings where the pursuit of knowledge is viewed as a spiritual and moral journey that every individual must undertake; and (3) the poem's relevance in modern times, encouraging younger generations to appreciate the learning process and strive for knowledge. These findings have implications for developing more holistic and transformative educational programs. Despite challenges such as resource limitations and the complexity of adapting classical concepts, this research makes a significant contribution to theoretical frameworks for academic exchange programs and learning models integrating physical mobility with digital platforms.   تتناول هذه الدراسة الجوانب البلاغية في قصيدة «سافر تجد عِوَضًا عمَّن تُفارِقُه» للإمام الشافعي لفهم روح طلب العلم في التقليد الإسلامي. ومن خلال استخدام التحليل البلاغي والتأويل (الهرمنيوطيقي)، اعتمدت المنهجية النوعية الوصفية بأسلوب تحليل المحتوى. وقد كشفت النتائج عن ثلاثة محاور رئيسية: (1) استعمال لغة جميلة ومتعددة الطبقات، وتوظيف أساليب بلاغية متنوعة مثل الاستعارة والتشخيص لتأكيد أهمية العلم؛ (2) معانٍ فلسفية عميقة، حيث يُنظر إلى طلب العلم بوصفه رحلة روحية وأخلاقية ينبغي لكل فرد أن يخوضها؛ و(3) صلة القصيدة بالواقع المعاصر، إذ تحث الأجيال الشابة على تقدير عملية التعلم والسعي الجاد لاكتساب المعرفة. ولتلك النتائج آثار على تطوير برامج تعليمية أكثر شمولية وتحويلية. ورغم وجود تحديات مثل محدودية الموارد وصعوبة تكييف المفاهيم التراثية، فإن هذه الدراسة تُسهم إسهامًا مهمًّا في إثراء الأطر النظرية لبرامج التبادل الأكاديمي ونماذج التعليم التي تدمج بين التنقّل الميداني والمنصات الرقمية.   Penelitian ini mengkaji aspek retorika dalam puisi "Safir Tājid ‘Iwaḍon ‘Amman Tufāriquhu" karya Imam Syafi’i untuk memahami semangat menuntut ilmu dalam tradisi Islam. Dengan menggunakan analisis retorika dan hermeneutik, metodologi yang diterapkan adalah kualitatif-deskriptif dengan teknik analisis isi. Temuan penelitian ini mengungkapkan tiga poin utama: (1) penggunaan bahasa yang indah, berlapis, dan berbagai teknik retorika seperti metafora dan personifikasi untuk menegaskan pentingnya ilmu; (2) makna filosofis yang mendalam, di mana pencarian ilmu dipandang sebagai perjalanan spiritual dan moral yang harus ditempuh setiap individu; dan (3) relevansi puisi ini pada masa modern, yang mendorong generasi muda untuk menghargai proses belajar dan berjuang meraih ilmu. Temuan ini memiliki implikasi bagi pengembangan program pendidikan yang lebih holistik dan transformatif. Meskipun terdapat tantangan seperti keterbatasan sumber daya dan kompleksitas dalam mengadaptasi konsep-konsep klasik, penelitian ini memberikan kontribusi signifikan terhadap kerangka teori untuk program pertukaran akademik dan model pembelajaran yang mengintegrasikan mobilitas fisik dengan platform digital.